Using Porter's Strategic Model to Promote Sustainable Marketing In Light Of Behavioral Finance (An Analytical Study Of A Sample Of Small And Medium Enterprises In Najaf Governorate) - Al-Daamee, Waleed Abbas Jebur; Meala, Qhayser Ali Hadi; Al Zubaidi, Haidar Hamoudi Ali (Journal of Ecohumanism, 2024)
This paper determines the suitability of companies' activities that can contribute to enhancing their performance and achieving a large market share, especially in the field of diversifying funding sources. The purpose of this paper was to idintify the impact of Porter's five forces on enhancing sustainable marketing for the research sample companies. The paper was designed in light of adopting the descriptive analytical approach for the research variables and collecting data and information through the questionnaire tool distributed to the research sample companies. And using statistical analysis to reach the results, the study sample amounted to (21) companies operating in the field of tourism and travel. The results of the paper showed that there is a threat from new entrants in the tourism industry due to the presence of many competing companies. Companies had to develop a strategy on how to attract and retain customers to avoid switching from one company to another by using Porter's model to promote sustainable marketing and using behavioral financing sources. which is reflected in their competitive position due to the presence of different companies.